Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1196/annals.1392.006
|View full text |Cite
|
Sign up to set email alerts
|

The Cdx‐Hox Pathway in Hematopoietic Stem Cell Formation from Embryonic Stem Cells

Abstract: Embryonic stem cells (ESCs) differentiated in vitro will yield a multitude of hematopoietic derivatives, yet progenitors displaying true stem cell activity remain difficult to obtain. Possible causes are a biased differentiation to primitive yolk sac-type hematopoiesis, and a variety of developmental or functional deficiencies. Recent studies in the zebrafish have identified the caudal homeobox transcription factors (cdx1/4) and posterior hox genes (hoxa9a, hoxb7a) as key regulators for blood formation during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…This phenotype was validated by reduction in alkaline phosphatase expression and upregulation of Hoxb4 and Cdx4. Increased Hoxb4 and Cdx4 expression levels are known to enhance the clonogenic potential of EB-derived cells during hematopoietic differentiation [49,50]. Recent evidence suggests that Cdx4 is upregulated in 23% of AML patients, with preferential expression shown in primitive stem and progenitor cells.…”
Section: Transcriptional Flux Of Hox Network In Es Cell Modelsdiscussionmentioning
confidence: 99%
“…This phenotype was validated by reduction in alkaline phosphatase expression and upregulation of Hoxb4 and Cdx4. Increased Hoxb4 and Cdx4 expression levels are known to enhance the clonogenic potential of EB-derived cells during hematopoietic differentiation [49,50]. Recent evidence suggests that Cdx4 is upregulated in 23% of AML patients, with preferential expression shown in primitive stem and progenitor cells.…”
Section: Transcriptional Flux Of Hox Network In Es Cell Modelsdiscussionmentioning
confidence: 99%
“…The most notable platform for this type of study is the AinV cell line developed by Kyba and Daley (Kyba et al, 2002) to induce expression of the homeobox family gene HoxB4 . Along with several other homeobox factors, HoxB4 is a potent stimulator of stem/progenitor cell output (Sauvageau et al, 1995; Helgason et al, 1996; Pineault et al, 2002; Lengerke et al, 2007). This cell line employs engineered loci on the X chromosome and chromosome 6 to allow single-site targeted insertion of a transgenic construct, with tetracycline-mediated (“tet-on”) transactivation via expression of the reverse tet-transactivator protein from the constitutive ROSA26 promoter.…”
Section: Controlling Stem/progenitor Cell Output Through Manipulationmentioning
confidence: 99%
“…For this purpose, we focused on the nodal/TGFb, BMP4 and VEGF pathways as they are known to play a role at different stages of mesoderm induction and hematopoietic specification in vivo (Conlon et al, 1994;Liu et al, 1999;Winnier et al, 1995) and have been shown to function in a similar capacity in vitro (Lengerke et al, 2007;Ng et al, 2005;Nostro et al, 2008). Using an ESC line carrying the enhanced green fluorescent protein cDNA targeted to the brachyury (T) gene [T-EGFP (Fehling et al, 2003)], we evaluated both T-EGFP and Flk1 expression over time to monitor mesoderm induction and specification.…”
Section: Temporal Development Of Hematopoietic Progenitor Populationsmentioning
confidence: 99%